Rent appropriation in global value chains: The past, present, and future of intangible assets. (31st March 2022) - Buckley, Peter J.; Strange, Roger; Timmer, Marcel P.; de Vries, Gaaitzen J.
Abstract: Research Summary: The argument of this article is that global strategy research should devote greater attention to rent appropriation in global value chains (GVCs). We discuss the concept of intangible assets, emphasize their scalability at low marginal cost and highlight strategies for the appropriation of rents from these assets. Returns captured by intangible assets are shown to be much greater than those captured by tangible assets in GVCs of manufactured products. Regions in the world are found to be specializing in different GVC stages, with China rising as a key location for rent generation in upstream and production activities. We conclude that the rents from intangible assets are major drivers of economic development and of corporate success and offer insights into rent appropriation trends in the future. Managerial Summary: Intangible assets include computerized information (such as databases and software), innovative property (such as patents, trademarks, and copyrights), and economic competencies (such as brand equity and organizational capital). Our analysis shows that the returns to intangible assets in the GVCs of manufactured goods have risen substantially in importance over the past 20 years. A further finding is that within GVCs, the rent share of upstream stages has been increasing at the expense of rents shares of both the production and downstream stages. These findings suggest that the effective deployment, management, and protection of intangible assets is of critical importance to the ability of firms to create and maintain sustainable competitive advantages in global markets. In GVCs, intangibles matter, big time!